Lactobacillus plantarum survival during the osmotic dehydration and storage of probiotic cut apple - Emser, Kassandra (2017)
The feasibility to incorporate Lactobacillus plantarum in apple cubes during the osmotic dehydration (OD) was investigated. The effects of 40 and 60 °Brix osmotic solutions of sucrose or sorbitol on the viability of L. plantarum during the OD at 37 °C and 1013 or 150 mbar was evaluated. The storage at 4 °C and a quick simulation (2 h) of the digestion of probiotic apple cubes through the gastro-intestinal tract were also performed and the viability of the probiotic evaluated. Lactobacillus plantarum got incorporated in the osmotically apple cubes (107–108 cfu/g) with preference for 40 °Brix solutions and it maintained the viability of 107 cfu/g during a 6 day-storage at 4 °C. L. plantarum also survived (107 cfu/g) during the simulation of the digestion. Colour changes of the probiotic apple cubes occurred after OD and storage. Therefore, osmotically dehydrated apple cubes incorporated with L. plantarum could be a new probiotic food.